Genetic diversity of domestic and commercial turkey breeds: assessment using RAPD-PCR technique - Al-Barzinji, Yousif M.S.; Fatah, Aram O. (Malaysian Society of Applied Biology, 2016)
This study was undertaken on 50 local (Black, Red and Narragansett) and 26 commercial turkey breeds (Black, White and Red). Out of twenty random primers used, twelve were able to amplify and showed bands. The total fragment number over all the turkey samples was 324 with size range of fragments from 220 to 2800 bp. Polymorphic fragments and unique bands in all breeds were 60 and 18, respectively. The Nei’s gene diversity for overall breeds averaged 0.44. The genetic distance among all turkey breeds ranged from 0.144 to 0.575. The higher genetic distance in local breeds was 0.667 between both (Black and Red) and (Black and Narragansett). On the other hand, the lowest distance was 0.269 between the Narragansett and Red breeds. The overall dendrograms showed three main clusters, the first cluster branch consisted of (local and commercial) black breeds; the second cluster included (local and commercial) Red breeds, while the third cluster included local Narragansett and commercial White breeds. These results showed that the three local turkey breeds are independent to one another.